The Correlation between Smoking Environment to Pregnant Women who Affected by Smoke to The Incidence of Low Birth Weight Babies in Surakarta - Ahadina Rahma Zulardi; Diffah Hanim; Amelya Augusthina Ayusari (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background: Smoking has dangerous effect on health, not only for active smoker, but also for passive smoker. One negative effect of cigarette smoke for pregnant women and fetuses is lower than normal fetal weight. Smoking has worse effect, because it affects the next development of the fetus / infant. This study aims to know the correlation between smoking environments to pregnant women exposed to cigarette smoke to the low birth weight baby case in Surakarta. Methods: The research was conducted in September to October 2014 at RSUD Dr. Moewardi and RSUD Ngipang, Surakarta. This is an observational analytic research with cross sectional design. A Sampling study was done in incidental sampling with the inclusion criteria : 1). Low Birth Weight Baby (LBWB) and non-LBWB 2). alive infant 3.) single fetus 4). Primigravida. Respondent filled in the biographical data sheet and informed consent forms as a sign of approval and filled out questionnaire of passive smokers. A total of 35 data was obtained and analyzed using bivariat Chi-Square test analysis. Results: Pregnant women with heavy smokers environment have LBWB risk 21 667 times higher than pregnant women with light smoker environment (OR=21.667). Pregnant women with medium smokers environment have LBWB risk 3.25 times higher than pregnant women with light smoker environment (OR=3.250). Conclusions: There is a significant relationship between pregnant women who are exposed to cigarette smoke on smoker environment and low birth weight baby case. Pregnant women who were medium and heavy passive smokers have a greater risk than a light passive smoker Keywords: Low birth weight, pregnant women, passive smoker.